Hubungan Stres dengan Temporomandibular Disorder pada Mahasiswa Fakultas Kedokteran Gigi Universitas Andalas - Zhafarina Adani Atika; Eni Rahmi; Arymbi Pujiastuty (Andalas Dental Journal, 2020)
Stress is the body’s response to various stressors that demand individual adjustment. College students often experience stress during their studies. Excessive stress can interfere the normal function of the body that can trigger the onset of temporomandibular disorder. The study aims to determine the relationship between stress and temporomandibular disorder in Dental Students of Andalas University. This study was observational analytic with the cross sectional design. The respondent was selected through purposive sampling technique with the total respondent were 67 students. The responden’s stress was measured with Student Stress Inventory (SSI) questionnaire, while temporomandibular disorder was examined and determined by RDC/TMD Axis I. The results showed that 37 respondents (55,2%) had mild stress and 30 respondents (44,8%) had moderate stress. The prevalence of temporomandibular disorder was 61,2%. Disc displacement with reduction was the most dominant diagnosis of temporomandibular disorder. Statistical chi-square test results obtained p=0,019 (p<0,05) that meant there was a significant relationship between stress and temporomandibular disorder in Dental Students of Andalas University. The result of this study concluded that there was relationship between stress and temporomandibular disorder.